Risk of incident cardiovascular disease in people with periodontal disease: A systematic review and meta‐analysis - Harriet Larvin; Jing Kang; Vishal R. Aggarwal; Sue Pavitt; Jianhua Wu (Wiley, 2021)
Abstract Objectives Cardiovascular disease (CVD) is a major cause of mortality; periodontal disease (PD) affects up to 50% of the world's population. Observational evidence has demonstrated association between CVD and PD. Absent from the literature is a systematic review and meta‐analysis of longitudinal cohort studies quantifying CVD risk in PD populations compared to non‐PD populations. To examine the risk of incident CVD in people with PD in randomised controlled trials and longitudinal cohort studies. Material and Methods We searched Medline, EMBASE and Cochrane databases up to 9th Oct 2019 using keywords and MeSH headings using the following concepts: PD, CVD, longitudinal and RCT study design. CVD outcomes included but were not restricted to any CVD, myocardial infarction, coronary heart disease (CHD) and stroke. Diagnosis method and severity of PD were measured either clinically or by self‐report. Studies comparing incident CVD in PD and non‐PD populations were included. Meta‐analysis and meta‐regression was performed to determine risk of CVD in PD populations and examine the effects of PD diagnosis method, PD severity, gender and study region. Results Thirty‐two longitudinal cohort studies were included after full text screening; 30 were eligible for meta‐analysis. The risk of CVD was significantly higher in PD compared to non‐PD (relative risk [RR]: 1.20, 95% CI: 1.14-1.26). CVD risk did not differ between clinical or self‐reported PD diagnosis (RR = 0.97, 95% CI: 0.87-1.07,). CVD risk was higher in men (RR: 1.16, 95% CI: 1.08-1.25) and severe PD (RR: 1.25, 95% CI: 1.15-1.35). Among all types of CVD, the risk of stroke was highest (RR = 1.24; 95% CI:1.12-1.38), the risk of CHD was also increased (RR = 1.14; 95% CI:1.08-1.21). Conclusion This study demonstrated modest but consistently increased risk of CVD in PD populations. Higher CVD risk in men and people with severe PD suggests population‐targeted interventions could be beneficial.